Brave New Reductionism: TQM as Ethnocentrism - Dennis, Dion (Education Policy Analysis Archives, 1995)
At century's end, practices at institutions of higher education are regularly subjected to a numbing array of stresses. Under the umbrella of fiscal austerity, intensified regimes of surveillance, in the form of corporatist management philosophies such as Total Quality Management (TQM), have been widely imposed. TQM proponents now advocate the total managementof human thought and identity. In a blatantly econometric and ethnocentric discourse where human variability is a "virus" to be "eliminated" under a war metaphor, nothing less than the future of independent intellectual work is at stake. This essay primarily explores how the theoretical roots and contemporary tropes of TQM shape a range of TQM-effects.